A study on the post-evaluation system of functional upgrading and transformation for old urban industrial areas. Issue 1 (December 2020) - Yue, X Y; Pan, H Y; Tang, P; Sun, H; An, Y
Abstract: At the beginning of the 21st century, China began to transform and upgrade the old urban industrial areas. At present, it is relatively lack to research the post-evaluation system of functional upgrading and transformation for old urban industrial areas. This paper chooses and analyzes 24 typical projects of regeneration and transformation for old urban industrial areas through literature research. On the basis of analyzing the relevant literature research, policy implementation and practice results of typical projects, this paper proposes a post-evaluation system with comprehensive influence as the target and 5 influence dimensions and 21 evaluation factors through combining qualitative and quantitative techniques. Based on this, the connotation of evaluation factors is analyzed, so as to form a practical post-evaluation system of comprehensive influence.